Paciente masculino de 46 años con enfermedad pulmonar obstructiva crónica. - Macías Mora, Lady Ruth (2021)
Chronic obstructive pulmonary disease (COPD) is a pulmonary pathology that consists of chronic inflammation that does not allow the normal flow of air through the lungs. Your biggest risk factor is cigarette smoking or frequent exposure to irritating gases. People with chronic bronchitis and pulmonary emphysema are potential candidates for developing COPD. People usually have symptoms when lung damage is severe and increases over time, and even more so when in contact with cigarettes or irritating gases. Among the most common symptoms is energy dyspnea, and when it is more advanced, wheezing and elongated expirations are characteristic symptoms. The treatment of COPD must be carried out in a progressive and staggered manner and this is given according to the severity of the patient. The patient should be educated regarding prevention such as avoiding cigarette consumption, staying away from irritating, toxic, and harmful odors, as well as performing physical exercises to strengthen the lungs.